Advances in geophysics proceedings of a symposium held at Charlottesville, Virginia, April 8-14, 1973 - Frankiel, Francois N.; Munn, R. E. (Advances in geophysics ;, 1974)
ADVANCES IN GEOPHYSICS VOLUME 18A.